Implementasi Media Pembelajaran Digital Learning Untuk Menciptakan Cakap Digital Di SMAN 19 Surabaya - Laila Puspitasari; Tri Indah Wahyuningtyas; Kharisma Nur Afifah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Digital learning media is one of the supporting tools of learning media. Learning media vary greatly, one of which is digital learning media where this media is technology-based in its use. The use of digital learning media is one of the efforts to train and educate students to be digitally proficient in accordance with the program launched by the Ministry of Communication and Information in 2021 where all Indonesian citizens are expected to be able to understand and understand digital. Therefore, SMAN 19 Surabaya implements teaching and learning activities using digital learning media. This high school has used digital learning media ranging from teaching and learning activities every day, midterm assessments, daily assessments, end-of-semester assessments and even filling out the attendance list. This encourages SMAN 19 Surabaya students to become digitally proficient The results of this implementation are able to make SMAN 19 Surabaya students have excellent knowledge, insight and experience about the digital world in education.